A c-Src Inhibitor Peptide Based on Connexin43 Exerts Neuroprotective Effects through the Inhibition of Glial Hemichannel Activity - Gangoso, Ester; Talaverón, Rocío; Jaraíz-Rodríguez, Myriam; Domínguez-Prieto, Marta; Ezan, Pascal; Koulakoff, Annette; Medina, José M.; Giaume, Christian; Tabernero, Arantxa (Frontiers in Molecular Neuroscience, 2017)
The non-receptor tyrosine kinase c-Src is an important mediator in several signaling pathways related to neuroinflammation. Our previous study showed that cortical injection of kainic acid (KA) promoted a transient increase in c-Src activity in reactive astrocytes surrounding the neuronal lesion. As a cell-penetrating peptide based on connexin43 (Cx43), specifically TAT-Cx43266-283, inhibits Src activity, we investigated the effect of TAT-Cx43266-283 on neuronal death promoted by cortical KA injections in adult mice. As expected, KA promoted neuronal death, estimated by the reduction in NeuN-positive cells and reactive gliosis, characterized by the increase in glial fibrillary acidic protein (GFAP) expression. Interestingly, TAT-Cx43266-283 injected with KA diminished neuronal death and reactive gliosis compared to KA or KA+TAT injections. In order to gain insight into the neuroprotective mechanism, we used in vitro models. In primary cultured neurons, TAT-Cx43266-283 did not prevent neuronal death promoted by KA, but when neurons were grown on top of astrocytes, TAT-Cx43266-283 prevented neuronal death promoted by KA. These observations demonstrate the participation of astrocytes in the neuroprotective effect of TAT-Cx43266-283. Furthermore, the neuroprotective effect was also present in non-contact co-cultures, suggesting the contribution of soluble factors released by astrocytes. As glial hemichannel activity is associated with the release of several factors, such as ATP and glutamate, that cause neuronal death, we explored the participation of these channels on the neuroprotective effect of TAT-Cx43266-283. Our results confirmed that inhibitors of ATP and NMDA receptors prevented neuronal death in co-cultures treated with KA, suggesting the participation of astrocyte hemichannels in neurotoxicity. Furthermore, TAT-Cx43266-283 reduced hemichannel activity promoted by KA in neuron-astrocyte co-cultures as assessed by ethidium bromide uptake assay. In fact, TAT-Cx43266-283 and dasatinib, a potent c-Src inhibitor, strongly reduced the activation of astrocyte hemichannels. In conclusion, our results suggest that TAT-Cx43266-283 exerts a neuroprotective effect through the reduction of hemichannel activity likely mediated by c-Src in astrocytes. These data unveil a new role of c-Src in the regulation of Cx43-hemichannel activity that could be part of the mechanism by which astroglial c-Src participates in neuroinflammation.